Upregulation of hsa_circ_0000745/hsa_circRNA_101996 in peripheral blood monocytes is associated with coronary heart disease - Li Shanshan; Shi Miaomiao; Gele Teri; Zhang Aimin; Li Wenyi; Sun Yi; Wang Chunyan; Zhao Jie; Pei Lin; Liu Jian; Jia Mei (Journal of Laboratory Medicine)
Circular RNAs (circRNAs) are known to be associated with cardiovascular diseases. At present, an ideal biomarker for the early diagnosis of coronary heart disease (CHD) is still lacking.